Impacto económico del proceso de comercialización de energía eléctrica en las finanzas de la corporación nacional de electricidad (CNEL) sistemas Quevedo. Años 2011-2012 - Alvarez Pilay, Carlos Patricio (2013)
It is considered essential for the Government of Ecuador, in the context of the new economic model applied, public enterprises, among which is the National Electricity Council has as its vision to be the public enterprise distribution and marketing of electricity from Ecuador reference quality, coverage and efficiency, with the appropriate use of technology and human talent to contribute to good living. This research may require that 43.47% of respondents believe that it is well suited for the electric service provided by CNEL also the highest level of satisfaction, a result of the relationship with the marketing area, the speed is given by in response to customer requests. 33.9% of customers CNEL Quevedo attributed a rating of 5 for satisfaction because sound administrative management of this company, can be determined that there is a good performance management system CNEL Quevedo. The 41.46% of customers said that almost always people who care provides a reliable and according to their needs, in addition to the 45.98% is excellent how the company solves its drawbacks. Comparing the relationship with the Regional Quevedo CNEL CNEL Guayas Rivers, has to be the invoiced value represents 23.7% in 2011 of the regional total. By 2012, this proportion decreases to 23.2%. Earnings in the period 2011 were USD 5,646,854, represented by 23.9% of expenditures. By 2012, these increased significantly to U.S. $ 16,790,137, equivalent to 58.6 %